THE SIGNIFICANCE AND PROSPECTS OF COOPERATION BETWEEN UZBEKISTAN AND TURKEY - Azamat Normuradovich Makhmudov; Shohjakhon Isokov (Modern American Journals, 2025)
In this article, the history of international relations between the Uzbek and Turkish nations, as well as the economic achievements attained through their cooperation, are analyzed. The author divides the period of Uzbek-Turkish cooperation into three stages for detailed examination
Keywords: Independence, cooperation, agreement, embassy, economic opportunities, joint enterprise, politics, science and technology, tourism, education.